Class Size in English Language Teaching: Teacher's Perspective - Yahya, Amalia; A. Zainuddin, Andi Husni; Hartina, St. (Institut Agama Islam Negeri Palopo, 2024)
This qualitative study investigates the impact of class size variability on the teaching process within the English Language Teaching (ELT) context at UPT SP SDN 25 Pae-Pae, Wasuponda. Through in-depth interviews with English language teachers, the research aims to gain insights into teachers' perspectives and experiences regarding the influence of class size on instructional practices and student outcomes. The findings reveal significant disparities between large and small classes, with larger classrooms offering advantages in facilitating interactive and engaging learning experiences, while smaller classrooms present challenges, particularly during interactive sessions. Classroom management strategies emerged as crucial in addressing challenges in both large and small classroom environments, ensuring a conducive learning environment for all students. Additionally, the study highlights the psychological and social impacts of class size and learning environment conditions on students, emphasizing the importance of tailored approaches and adequate facilities in promoting positive social interactions and collaborative learning experiences. Overall, the research underscores the importance of adaptive teaching practices and continuous professional development in meeting the diverse needs of students across varying class sizes and learning contexts within ELT settings.